Pengaruh Pemanfaatan Jam Belajar Di Luar Sekolah DanPendampingan Belajar Orang Tuaterhadap Hasil Belajar Siswa Di Sd 4 Pasuruhan Lor Kecamatan Jati Kabupaten KudusTahun Ajaran 2014/2015 - Sari, Silviana; , Drs. Achmad Fathoni, M.Pd (2015)
Silviana Sari, A 510 100 235, Influence Utilization Learning Outside School Hours Learning and Mentoring Parents Against Student Results In SD 4 Pasuruhan Lor Jati subdistrict Holy District School Year 2014/2015. Thesis. S1 Studies Program Elementary School Teacher Education, the Faculty of Education, University of Muhammadiyah Surakarta. 2015. The purpose of this study was to determine the effect of the use outside of school hours learning and mentoring learn the parents of the student learning outcomes in SD 4 Pasuruhan Lor Jati subdistrict Holy District Academic Year 2014/2015. The design study is quantitative descriptive. The sample in this study are are 15 students in grade III and 11 grade IV SDN 4 Pasuruhan Lor. Data collection was conducted by questionnaire or questionnaires, opservasi and documentation. Results of the study are presented as follows: from the calculation results obtained t value of 3,283 with a significance level of 0.003 <0.05 means that outside of school hours learning can improve learning outcomes. From the calculation results obtained t value of 17 090 with a significance level of 0.000 <0.05 means that a parent mentoring learning can improve learning outcomes. From the test results obtained f calculated F value of 428 216 with a probability of 0.000 <0.05. Based on the test coefficient of determination (R2) of 0.987, which means 98% of the variation of all the independent variables outside of school hours learning, mentoring learn the elderly and dependent variables of learning outcomes. While the remaining 2% is explained by other variables that are not proposed in this study.